2019
DOI: 10.3389/fendo.2019.00373
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Ion Channel Piezo1 Regulates Diet-Induced Adipose Inflammation and Systemic Insulin Resistance

Abstract: Adipocytes function as an energy buffer and undergo significant size and volume changes in response to nutritional cues. This adipocyte plasticity is important for systemic lipid metabolism and insulin sensitivity. Accompanying the adipocyte size and volume changes, the mechanical pressure against cell membrane also changes. However, the role that mechanical pressure plays in lipid metabolism and insulin sensitivity remains to be elucidated. Here we show that Piezo1, a mechanically-activated cation channel sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 53 publications
(50 reference statements)
2
40
0
Order By: Relevance
“…For this patient, the decrease in fasting and post-prandial insulin level was not consistent with typical T2DM, suggesting that there may be a specific relationship between DHS and the onset of diabetes mellitus. Recent studies indicated that PIEZO1 is a mechanically activated ion channel that might mediate pressure-induced pancreatitis and regulate diet-induced systemic insulin resistance (23,24). However, there was no evidence proving the mutation on the PIEZO1 gene could directly affect the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For this patient, the decrease in fasting and post-prandial insulin level was not consistent with typical T2DM, suggesting that there may be a specific relationship between DHS and the onset of diabetes mellitus. Recent studies indicated that PIEZO1 is a mechanically activated ion channel that might mediate pressure-induced pancreatitis and regulate diet-induced systemic insulin resistance (23,24). However, there was no evidence proving the mutation on the PIEZO1 gene could directly affect the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Histone protein was extracted using the EpiQuik Total Histone Extraction Kit from EpiGentek. Western blot was performed following a standard protocol ( 14 , 74 , 85 ). For IP, protein lysates were incubated with indicated antibodies at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…EpiGentek. Western blot was performed following a standard protocol (14,74,85). For immunoprecipitation, protein lysates were incubated with indicated antibodies at 4 o C overnight.…”
Section: Western Blot and Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Piezo1 channel is a newly discovered mechanosensitive ion channel that gives cells the ability to convert mechanical signals into intracellular signals [4]. A large amount of evidence supports that Piezo1 is involved in regulating in ammation induced by mechanical stress [5][6][7][8]. Piezo1 is mainly located in the plasma membrane, and it has also been reported in the endoplasmic reticulum, cytoplasmic compartment and nuclear envelope near the nucleus [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%